ANALYSIS OF THE INFLUENCE OF WORK DISCIPLINE, WORK FACILITIES AND WORK COMPETENCIES ON PERFORMANCE ACHIEVEMENT WELL SERVICE FUNCTION EMPLOYEES AT PT PERTAMINA HULU ROKAN PANGKALAN MILK FIELD - Musawir Da'i; Yeni Absah; Syafrizal Helmi Situmorang (CV. Radja Publika, 2023)
This research aims to determine and analyze the influence of Work Discipline, Work Facilities and Work Competence on the performance of Well Service employees at PT Pertamina Hulu Rokan Pangkalan Susu Field. The method used in this research is a descriptive method with a quantitative approach using multiple linear regression techniques. The population in this study was 96 employees with a sample of 66 respondents. The data analysis used is Validity Test, Reliability Test, Classic Assumption Test (Normality Test, Heteroscedasticity Test and Multicollinearity Test), Hypothesis Test (T Test, F Test), Determination Test and Multiple Linear Regression Analysis. The results of this research show that partially Work Discipline has a positive and significant effect on performance with a value of tcount > ttable, namely 3,393 > 1.998 and a Sig < α value, namely 0.001 < 0.05. Meanwhile, partially, Work Facilities do not have a positive and significant effect on performance with a value of tcount < ttable, namely 1.089 < 1.998 and a value of Sig > α, namely 0.280 > 0.05. Partial Job Competence also shows that there is no positive and significant influence on performance with a value of tcount < ttable, namely 0.635 < 1.998 and a value of Sig > α, namely 0.528 > 0.05. Simultaneously, Work Discipline, Work Facilities and Work Competence have a positive and significant effect on performance with a value of fcount > ftable, namely 17.594 > 2.751 and a value of Sig < α, namely 0.000 < 0.05. The contribution of Work Discipline, Work Facilities and Work Competence to performance together is 43%, while the remaining 57% is influenced by other variables not examined in this research.